Substation Fault Diagnosis Based on Time Sequence Fuzzy Petri Net - Haiying Dong; Xiaonan Li (Institute of Advanced Engineering and Science, 2013)
As the 750kV substation has the characteristics like timing inconsistency, dual protection configuration and uncertain diagnosis result, a fault diagnosis method of substation with redundant protection configuration based on time sequence fuzzy Petri nets is proposed. In this method, redundant knowledge about fault component is represented by using two sets of protective information. On that basis, component redundant diagnosis-model based on time sequence fuzzy Petri net is constructed, which can be decomposed into main and redundant subnet-model, in which initial-information credibility is determined by using information-entropy, the time sequence constraint is checked and initial-information credibility is corrected by using the relationship between acted protection and breaker. Compared with fuzzy Petri net diagnosis method taking no account of time sequence factor, the proposed method can not only identify the malfunction information, but also obtain a certain result. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2528